###### Advertisements

###### Advertisements

Choose the correct alternative:

If y = `(1 - x)^2/x^2`, then `("d"y)/("d"x)` is

#### Options

`2/x^2 + 2/x^3`

`- 2/x^2 + 2/x^3`

`- 2/x^2 - 2/x^3`

`- 2/x^3 + 2/x^2`

###### Advertisements

#### Solution

**`- 2/x^3 + 2/x^2`**

#### APPEARS IN

#### RELATED QUESTIONS

Find the derivatives of the following functions with respect to corresponding independent variables:

g(t) = t^{3} cos t

Find the derivatives of the following functions with respect to corresponding independent variables:

y = tan θ (sin θ + cos θ)

Differentiate the following:

y = cos (tan x)

Differentiate the following:

y = `root(3)(1 + x^3)`

Differentiate the following:

F(x) = (x^{3} + 4x)^{7}

Differentiate the following:

y = 4 sec 5x

Differentiate the following:

y = (2x – 5)^{4} (8x^{2} – 5)^{–3}

Differentiate the following:

y = sin^{2}(cos kx)

Differentiate the following:

y = `"e"^(xcosx)`

Find the derivatives of the following:

y = `x^(logx) + (logx)^x`

Find the derivatives of the following:

If cos(xy) = x, show that `(-(1 + ysin(xy)))/(xsiny)`

Find the derivatives of the following:

`tan^-1 = ((6x)/(1 - 9x^2))`

Find the derivatives of the following:

x = `"a" cos^3"t"` ; y = `"a" sin^3"t"`

Find the derivatives of the following:

Find the derivative of `sin^-1 ((2x)/(1 + x^2))` with respect to `tan^-1 x`

Find the derivatives of the following:

If y = e^{tan–1}x, show that (1 + x^{2})y” + (2x – 1)y’ = 0

Find the derivatives of the following:

If sin y = x sin(a + y), the prove that `("d"y)/("d"x) = (sin^2("a" + y))/sin"a"`, a ≠ nπ

Choose the correct alternative:

`"d"/("d"x) (2/pi sin x^circ)` is

Choose the correct alternative:

If y = cos (sin x^{2}), then `("d"y)/("d"x)` at x = `sqrt(pi/2)` is

Choose the correct alternative:

If f(x) = x tan^{-1}x then f'(1) is

Choose the correct alternative:

`"d"/("d"x) ("e"^(x + 5log x))` is